Determinants for Quantitative Sensory Testing and the Association with Chronic Musculoskeletal Pain in the General Elderly Population. Issue 7 (23rd July 2015) - de Kruijf, Marjolein; Peters, Marjolein J.; C. Jacobs, Leonie; Tiemeier, Henning; Nijsten, Tamar; Hofman, Albert; Uitterlinden, Andre G.; Huygen, Frank J. P. M.; van Meurs, Joyce B. J.
Abstract: Objective: Chronic musculoskeletal pain is accompanied by central sensitization, which can be determined with quantitative sensory testing (QST). In this study, we aim to investigate whether central sensitization, as measured by thermal QST, is detectable in community‐dwelling elderly individuals suffering from self‐reported chronic pain and identify determinants influencing thermal QST measurement analyses and interpretation. Methods: In 3, 936 participants of the Rotterdam Study, cold and warmth sensitivity and heat pain thresholds were determined using the thermo‐sensory analyzer TSA II (Medoc Advanced Medical Systems, Durham, NC, U.S.A.). Using Cox regression, associations were studied with chronic pain and potential determinants (body mass index [BMI], reaction speed, systolic and diastolic blood pressure, skin color, skin temperature, seasonal influence, depression, anxiety, atopic eczema, age at menarche, years since menopause, hormone replacement therapy (HRT) use during menopause, and reproductive lifespan). Results: In addition to the effect of age and gender on thermal sensitivity, darker skin color and the presence of atopic eczema were associated with higher sensitivity for heat pain. Cold sensitivity and warmth sensitivity thresholds were both influenced by BMI, reaction speed, skin temperature, season, depression, dark skin color, years since menopause, and reproductive lifespan. The presence of chronic pain was associated with 0.2 degrees lower heat pain threshold in all participants, and 0.3 degrees lower in individuals with chronic pain in more than 2 sites. Conclusion: Higher sensitivity for heat pain, one feature of central sensitization, is present in community‐dwelling elderly with chronic pain. Additional determinants should be considered when analyzing and interpreting QST measurements.